Optimization on parameter settings in determining warpage factors of a side-gated thin shallow part injection molding for PP, ABS & PC+ABS materials - Norshah Afizi, Shuaib (Praise Worthy Prize S.r.l., 2014)
Link to publisher's homepage at http://www.praiseworthyprize.com/